Assessment of Antimicrobial Activity, Reactivity and Non‐Linear Optical Properties of New Pyrazoline Derivatives having Pyrrole moiety. Issue 13 (30th August 2016) - Rawat, Poonam; Singh, R. N.; Sahu, Sangeeta; Niranjan, Priydarshni; Rani, Himanshu; Saxena, Rajat; Ahmad, Sartaj
Abstract: The purpose of this work is to study antimicrobial activity, chemical reactivity and non‐linear optical properties of newly synthesized and characterized 2‐pyrazoline derivatives having pyrrole moiety (4a–d ). 1, 3, 5‐trisubstituted pyrazoline derivatives (4a–c ) and 3, 5‐di‐aryl N‐substituted carbonyl pyrazoline derivative (4 d ) were synthesized by simple and efficient approach using cyclization reaction of chalcones (3a–c ) and aromatic hydrazine (AH ) / aromatic acid hydrazide (AAH ) in the presence of acid catalyst. The conformational investigation has been performed with the help of potential energy surface scan to understand and find out the stable conformers. All synthesized compounds have been characterized by spectroscopic ( 1 H and 13 C NMR, UV–Visible, FT–IR) techniques. Using self‐consistent reaction field (SCRF) method, the solvent‐induced effects on dipole moment (μ0 ), mean polarizability (|α0 |), anisotropy of polarizability (Δα ) and the first hyperpolarizability were studied for all compounds and found that the β0 values increase monotonically as the polarity increases. The β0 values of compounds are higher than the standard p ‐nitroaniline ( p ‐NA ) in solvent as well as in gas phase. The screening of the synthesized compounds for antimicrobial activity was performed against S. aureus, E. coli, C. Albicans and A. niger . The assayed compounds showed a good antibacterial (against gram positive and negative bacteria) and antifungal activity. Abstract : The work comprises synthesis of new pyrrole‐pyrazoline derivatives (4a–d) and study of their antimicrobial activity, chemical reactivity and non‐linear optical properties. Reactivity descriptors index of pyrrolyl chalcones favour pyrrole‐pyrazoilines formation through Michael addition. The β0 values of compounds are higher than the standard p ‐nitroaniline ( p ‐NA) in solvent as well as in gas phase, and found to increase monotonically as the polarity increases. The screening of the synthesized compounds showed a good antibacterial and antifungal activity.